New Realms of Agency: Promoting Peace Education and Gender Equity through Sport - Irene Kamberidou (Sport Science and Physical Education, [Ed. Luminita Georgescu ], Encyclopedia of Life Support Systems (EOLSS), Eolss Publishers, Oxford ,UK, 2012)
Encyclopedia of Life Support Systems  (EOLSS)  Kamberidou, Irene (2012). New Realms of Agency: Promoting Peace Education and Gender Equity through Sport, in Sport Science and Physical Education, [Ed. Luminita Georgescu ], Encyclopedia of Life Support Systems(EOLSS), Developed under the Auspices of the UNESCO, Eolss Publishers, Oxford ,UK, updated on a quarterly basis." (www.eolss.net). [Retrieved March 11, 2013][1]  [1] Κεφάλαιο (a treatise) σε εγκυκλοπαίδεια, με κριτές. Πρόσκληση (UNESCO PROJECT) να συντάξω κεφάλαιο στο Encyclopedia of Life Support Systems (EOLSS) από τον "Coordinating Editor of the EOLSS Section on Sport Science and Physical Education." (www.eolss.net)."